2014
DOI: 10.1016/j.redox.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic effects of nitrite supplementation in experimental inflammatory bowel disease

Abstract: BackgroundInorganic nitrate and nitrite have emerged as alternative substrates for nitric oxide (NO) generation in the gastrointestinal tract, and have shown to be protective against drug-induced gastric injury. The aim of this study was to investigate the preventive and therapeutic effects of nitrate and nitrite in a model of experimental colitis.MethodsColitis was induced in mice by administrating dextran sulfate sodium (DSS) with concurrent administration of nitrite (1 mM) or nitrate (10 mM) in the drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 60 publications
2
56
0
Order By: Relevance
“…While several studies conducted using animal models indicate the deleterious effect of NO, recent studies have shown that NO may also exert a protective effect against colitis [29][30][31][32] . One study conducted using a DSSinduced colitis model found that nitrite administration exerts both preventive and therapeutic effects in colonic inflammation [33] . More recently, iNOS deficiency enhanced the inflammation aggravation in an animal model of colitis through enhancing a Th17 differentiated subset [34] .…”
Section: No and Ibdmentioning
confidence: 99%
“…While several studies conducted using animal models indicate the deleterious effect of NO, recent studies have shown that NO may also exert a protective effect against colitis [29][30][31][32] . One study conducted using a DSSinduced colitis model found that nitrite administration exerts both preventive and therapeutic effects in colonic inflammation [33] . More recently, iNOS deficiency enhanced the inflammation aggravation in an animal model of colitis through enhancing a Th17 differentiated subset [34] .…”
Section: No and Ibdmentioning
confidence: 99%
“…While several studies conducted on animal models report the deleterious effect of NO, some recent studies have shown that NO may also exert protective effect against colitis [29][30][31][32]. Indeed, because of its strong bactericidal and cytostatic properties, high NO generation by iNOS may represent a protective mechanism [28].…”
Section: Nitric Oxide and Ibdmentioning
confidence: 99%
“…Indeed, because of its strong bactericidal and cytostatic properties, high NO generation by iNOS may represent a protective mechanism [28]. Recent study conducted on DSS-induced colitis model has shown that nitrite administration exerts both preventive and therapeutic effects in colonic inflammation [30]. More recently, iNOS deficiency was shown to aggravate inflammation in animal model of colitis through enhancing TH17 differentiation [31].…”
Section: Nitric Oxide and Ibdmentioning
confidence: 99%
“…Colitis was induced by adding DSS (2.5 %, molecular weight: 35000-55 000 Da; TdB Consultancy, Uppsala, Sweden) (Jädert et al 2014) to the drinking water (tap water) for 3, 5 or 7 days (see Section 2.3). The DSS-containing drinking water was made up fresh every second day to avoid bacterial contamination, and the consumption of water and food was monitored in all groups.…”
Section: Induction Of Colitismentioning
confidence: 99%
“…At day 7 7-10 after colitis induction mice were sacrificed by decapitation and their whole colons were removed. The reduction of colon length was used as another parameter to assess colonic inflammation (Jädert et al 2014). Care was taken not to stretch the colon.…”
Section: Induction Of Colitismentioning
confidence: 99%